IDENTITAS VIRTUAL REMAJA MELALUI KOSTUMISASI AVATAR (Studi Kualitatif Deskriptif Pada Remaja Pemain Game Online Roblox) - Teuku Erriyan Bagus Eko Prabowo; Syafrida Nurrachmi Febriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the use of avatars as a form of virtual identity for adolescents in the online game Roblox. Roblox, as a virtual world-based gaming platform, provides a space for its users to shape, display, and negotiate their identities through avatar customization features. This study used a qualitative approach with data collection techniques through in-depth interviews with ten informants aged 19 to 22 who are active Roblox users and have customized avatars. The results show that avatars are not only understood as visual characters in the game, but also as a form of presence, self-image, and representation of the player's identity in the digital space. Avatar customization becomes a means for informants to express taste, creativity, and the self-image they want to present to other players. Avatars also allow informants to construct various forms of identity, ranging from the real self, ideal self, alternative self, to alter egos that differ from everyday life. Furthermore, the use of Robux in avatar customization indicates a relationship between digital consumption and virtual identity formation. Paid items, custom avatars, and certain avatar appearances can become symbols of social status within the Roblox community. Thus, this study shows that avatars in Roblox play an important role in the process of adolescent self-representation in the virtual space. The virtual identity formed through an avatar is flexible, fluid, and can change according to desires, the context of the game, and the social response of the digital environment.